2022
DOI: 10.3389/fcell.2022.842320
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Polarization: A Novel Target of Exosome for Stroke Treatment

Abstract: The vast majority of cells in the human body are capable of secreting exosomes. Exosomes have become an important vehicle for signaling between cells. Exosomes secreted by different cells have some of the structural and functional properties of that cell and thus have different regulatory functions. A large number of recent experimental studies have shown that exosomes from different sources have different regulatory effects on stroke, and the mechanisms still need to be elucidated. Microglia are core members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 160 publications
0
13
0
Order By: Relevance
“…In addition, miRNAs that enter the exosomes through an active sorting mechanism can be absorbed by receptor cells, then regulated the biological function of receptor cells [ 40 ]. miRNAs such as miR-146a-5p, miR-192-5p, miR-146a-5p, and miR-34a in exosomes can affect the M1/M2 polarization of microglia [ 41 , 42 ]. Here, we found that exosomal miR-3613-3p in OGD-treated BMECs can be transferred to microglia and promote the polarization of glioma cells towards the M1-type.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miRNAs that enter the exosomes through an active sorting mechanism can be absorbed by receptor cells, then regulated the biological function of receptor cells [ 40 ]. miRNAs such as miR-146a-5p, miR-192-5p, miR-146a-5p, and miR-34a in exosomes can affect the M1/M2 polarization of microglia [ 41 , 42 ]. Here, we found that exosomal miR-3613-3p in OGD-treated BMECs can be transferred to microglia and promote the polarization of glioma cells towards the M1-type.…”
Section: Discussionmentioning
confidence: 99%
“…The polarization of M2 microglia is essential for the restoration of tissue homeostasis after inflammatory injury (28). Promoting the polarization of microglia from M1 to M2 ameliorates the progression of several neuroinflammatory diseases (6,29), suggesting a prospective therapeutic potential. Indeed, this dichotomous classification simplifies microglial activation, and multiple intermediate phenotypes between M1 and M2 phenotypes have been identified in recent years (30).…”
Section: Microglial Activationmentioning
confidence: 99%
“…The peak time points of cytokine expression differ in different cell polarization states. Promotion of the microglia M2 polarization is one method for exerting neuroprotective effects in ischemic stroke ( 41 ).…”
Section: Resident and Peripheral Immune Responses In Ischemic Strokementioning
confidence: 99%